Multivariate MOFs for laser writing of alloy nanoparticle patterns. Issue 18 (5th February 2020) - Ma, Ruiqian; Jiang, Haoqing; Wang, Chao; Zhao, Chengbin; Deng, Hexiang
Abstract : We report three methods for the synthesis of alloy nanoparticles by a laser in air, where three types of MOF precursors are used. Abstract : We report three methods for the synthesis of alloy nanoparticles by a laser in air, where three types of MOF precursors are used. Multivariate MOFs, containing different metals in the single crystal backbone, provide continuous tuning of the metal content and excellent uniformity of metal dispersion.